The Role of the Principal as a Supervisor in Improving Digital-Based Educational Quality at SMKN 2 Marabahan - Nor Azizah; Maya Madina; Widy Noviani; Sulistiyana Sulistiyana; Metroyadi Metroyadi (FKIP - Universitas Riau, 2026)
This qualitative descriptive study examines the principal's supervisory role in improving digital-based educational quality at SMKN 2 Marabahan during the Industrial Revolution 4.0 era. Data were collected through semi-structured interviews with the principal, 15 teachers, and three staff members, supplemented by 20 classroom observations and documentation analysis. Analysis followed Miles and Huberman's interactive model with triangulation and member checking for validity. Findings reveal that the principal functions as an innovative supervisor through three strategies: implementing a Learning Management System for systematic monitoring, developing industry-aligned programs (industrial classes and Vocational Industrial Work Training), and facilitating continuous teacher professional development with a developmental rather than evaluative approach. Results showed the school's national accreditation score increased from 83.5 to 91.5 (9.6% improvement), digital competency test pass rates rose from 78% to 92%, and graduate employment rates increased from 65% to 81%. These findings demonstrate that technology-adaptive supervision significantly enhances vocational education quality, suggesting that principals must integrate digital technologies and industry partnerships for effective vocational education transformation in the digital era.